Respiratory dysfunction in Parkinson's disease: a narrative review. Issue 4 (5th October 2020) - D'Arrigo, Andrea; Floro, Stefano; Bartesaghi, Francesca; Casellato, Chiara; Sferrazza Papa, Giuseppe Francesco; Centanni, Stefano; Priori, Alberto; Bocci, Tommaso
The presence of respiratory symptoms in Parkinson's disease (PD) has been known since the first description of the disease, even though the prevalence and incidence of these disturbances are not well defined. Several causes have been reported, comprising obstructive and restrictive pulmonary disease and changes in the central ventilatory control, and different pathogenetic mechanisms have been postulated accordingly. In our review, we encompass the current knowledge about respiratory abnormalities in PD, as well as the impact of anti-Parkinsonian drugs as either risk or protective factors. A description of putative pathogenetic mechanisms is also provided, and possible treatments are discussed, focusing on the importance of recognising and treating respiratory symptoms as a key manifestation of the disease itself. A brief description of respiratory dysfunctions in atypical Parkinsonism, especially α-synucleinopathies, is also provided. This review addresses current knowledge about respiratory dysfunctions in Parkinson's disease, from the aetiopathology to pharmacological and invasive treatments, describing the different clinical phenotypes https://bit.ly/2X7OLtN